2019
DOI: 10.4187/respcare.06896
|View full text |Cite
|
Sign up to set email alerts
|

Health-Literacy Training for First-Year Respiratory Therapy Students: A Mixed-Methods Pilot Study

Abstract: BACKGROUND: Respiratory therapists (RTs) should communicate with patients in a way that leads to patients understanding their discharge plans and medical device instructions. The teachback method is a patient-centered, health-literate technique that allows health care professionals to confirm patient understanding. The purpose of this mixed-methods pilot study was to measure the use of teach-back by first-year undergraduate RT students in a simulation-center experience after a 1-h teach-back skills training. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 22 publications
(24 reference statements)
0
13
0
Order By: Relevance
“…HCPs may even benefit from short training programs. Ogrodnick et al [45] piloted a one-hour HL and teach-back skills training session in a group of respiratory therapists; knowledge and communications scores increased significantly.…”
Section: Discussionmentioning
confidence: 99%
“…HCPs may even benefit from short training programs. Ogrodnick et al [45] piloted a one-hour HL and teach-back skills training session in a group of respiratory therapists; knowledge and communications scores increased significantly.…”
Section: Discussionmentioning
confidence: 99%
“…The interventions identified in the review totaled 19 strategies, divided into 5 subcategories (Table B ) : Expositive ( n = 18; 94.7%). Includes interventions that used instructional methods, such as lecture ( Ogrodnick et al, 2020 ), study session with presentation ( Trujillo & Figler, 2015 ) and lectures ( Niemi et al, 2018 ). Interactive ( n = 9; 47.4%).…”
Section: Resultsmentioning
confidence: 99%
“… Standardized patient or simulation ( n = 8; 42.1%). This included the use of simulated care with a standardized patient ( Marion et al, 2018 ), scenarios where participants played roles ( Mackert et al, 2011 ), and simulation centers ( Ogrodnick et al, 2020 ). Practices with actual patients ( n = 4; 21.1%).…”
Section: Resultsmentioning
confidence: 99%
“…In terms of medical eld organizational hierarchy, this study emphasizes the importance of teaching and intervention effects of health literacy courses in healthcare professional education. [37][38][39][40][41][42] In clinical and community elds, there have been studies on professional competence in health literacy with variegated practicing healthcare professionals or medical students as subjects; after implementing comprehensive teaching intervention on functional, interactive, and critical health literacy, the study found signi cant progress in knowledge, attitude, and skills. [24,33,43] Our study applied a similar curriculum design concept; we can see that comprehensive teaching module is a reliable and cogent teaching method in both clinical and school settings.…”
Section: Discussionmentioning
confidence: 99%